2019
DOI: 10.1136/ejhpharm-2019-001939
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous drug use in neonatal intensive care units

Abstract: ObjectivesIntravenous drug use in neonates is frequent and prone to medication errors. The aim of this study was to describe the intravenous drugs most frequently used in Spanish Neonatal Intensive Care Units (NICU), their preparation and the implementation rate of standardised concentration infusions.MethodsWe conducted an observational multicentre study based on a survey sent by email to nine Spanish NICUs during January and February 2018. We collected data describing the intravenous drugs frequently used in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…In fact, in our research we were able to validate the value of neonatal DDD for four of the five top antimicrobials. Even the combination of aminoglycosides with beta-lactams, the most commonly used in neonates with sepsis or suspected sepsis according to published data [ 22 ], coincides with the data for the two antibiotics (gentamicin and ampicillin) with the highest number of prescriptions in hospitalised neonates in our study centres [ 23 ].…”
Section: Discussionsupporting
confidence: 87%
“…In fact, in our research we were able to validate the value of neonatal DDD for four of the five top antimicrobials. Even the combination of aminoglycosides with beta-lactams, the most commonly used in neonates with sepsis or suspected sepsis according to published data [ 22 ], coincides with the data for the two antibiotics (gentamicin and ampicillin) with the highest number of prescriptions in hospitalised neonates in our study centres [ 23 ].…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, various risk reduction strategies are recommended to reduce harm when high-alert medications are used during medication administration. Examples of these strategies include standardising the preparation and administration of these medications with the involvement of a clinical pharmacist [ 46 , 49 ], implementing barcode medication administration safety and limiting the administration of high-alert medications to special authorised staff [ 46 , 50 ], improving access to information about these medications [ 46 ] and enforcing double checking when administering medications [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous drug use in NICUs is defined as a high-risk process. In a multicenter study conducted by NICU, it was found that 33% of 69 different intravenous drugs used in NICUs were not approved for neonates, 38% were high-risk, and only 63.5% were prepared and administered in standardized concentrations [ 14 ]. In our study, it is estimated that the administration of intravenous high-risk drugs may have an effect on the incidence of ADRs.…”
Section: Discussionmentioning
confidence: 99%